Monte-Carlo simulation of charge sharing in 2 mm thick pixelated CdTe sensor. (1st February 2023) - Jirsa, J.; Gecnuk, J.; Janoska, Z.; Jakovenko, J.; Kafka, V.; Marcisovsky, M.; Marcisovska, M.; Stanek, P.; Tomasek, L.; Vancura, P.
Abstract: Precise physical models of sensors are essential for developing high precision pixelated detectors. Advanced technologies allowed pixel electronics to be integrated in tens of micrometers pixel pitch. Such fine pixelated detectors suffer from charge sharing effect and, in high-Z materials, also from fluorescent photons traversing one or more pixels. This work presents a Monte-Carlo model of a 2 mm thick 70 μm pitch pixelated CdTe sensor designed for simulation of the absorption of X-ray photons from monochromatic X-ray photon beams. Charge diffusion across a pixel matrix was computed using a drift-diffusion model for each photon generating free electron-hole pairs. Based on the simulation outcome, we estimated the dependence of cluster size on photon energy and total charge distribution between neighboring pixels.